Razvoj prebivalstva v Ljubljanski urbani regiji = Population development in Ljubljana urban region - Dejan Rebernik (Dela, 2004)
The paper presents the maincharacteristic of population development and urbanisation processes inLjubljana and Ljubljana urban region. Up to the end of the seventies fastpopulation growth was a consequence of strong immigration from rural partsof Slovenia and the rest of Yugoslavia. In the eighties and ninetiesdeconcentration of population within the region with intensesuburbanisation and depopulation of inner city and older residentialneighbourhoods were the main urbanisation processes. In the second half ofthe nineties the highest population growth was recorded in dispersed ruralsettlements in the periphery of the region. In some parts of the inner cityreurbanisation and gentrification occurred.